2017
DOI: 10.1186/s12931-017-0530-0
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke challenges bone marrow mesenchymal stem cell capacities in guinea pig

Abstract: BackgroundCigarette smoke (CS) is associated with lower numbers of circulating stem cells and might severely affect their mobilization, trafficking and homing. Our study was designed to demonstrate in an animal model of CS exposure whether CS affects the homing and functional capabilities of bone marrow-derived mesenchymal stem cells (BM-MSCs).MethodsGuinea pigs (GP), exposed or sham-exposed to CS, were administered via tracheal instillation or by vascular administration with 2.5 × 106 BM-MSCs obtained from CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Cigarette smoke, a major risk factor for COPD, has been shown to reduce the repair potential of endothelial progenitor cells [139] and bone marrow mesenchymal stem cells by interfering with cell homing and proliferation capacities [140]. Thus, stem cell exhaustion might contribute to COPD pathogenesis by reducing the endogenous renewal and repair capacity of the lung by local as well as recruited cells.…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…Cigarette smoke, a major risk factor for COPD, has been shown to reduce the repair potential of endothelial progenitor cells [139] and bone marrow mesenchymal stem cells by interfering with cell homing and proliferation capacities [140]. Thus, stem cell exhaustion might contribute to COPD pathogenesis by reducing the endogenous renewal and repair capacity of the lung by local as well as recruited cells.…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…Dysfunctional PCs show excessive apoptosis and are unable to respond to external injuries to mediate proper lung tissue healing [26]. Previous results from our group showed in an experimental animal model, that short-term exposure to CS induced PCs dysfunction, affecting pulmonary homing and proliferation [27]. In vitro, CS altered the rate of proliferation, senescence, differentiation and migration capacity of PCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that cigarette smoke or cigarette smoke components have cytotoxic effects on stem cells. Exposure of short‐term cigarette smoke induced dysfunction to cell homing and cell survival of bone marrow‐derived mesenchymal stem cells . An in vitro study showed that exposure of human umbilical cord blood cells to 3–9 mM nicotine decreased cell proliferation in a dose dependent manner and increased apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of short-term cigarette smoke induced dysfunction to cell homing and cell survival of bone marrow-derived mesenchymal stem cells. 26 An in vitro study showed that exposure of human umbilical cord blood cells to 3-9 mM nicotine decreased cell proliferation in a dose dependent manner and increased apoptosis. 27 In addition, an in vivo study showed that the proliferation capacity of mesenchymal stem cells isolated from chronic smokers was about 2.5-fold less than that from non-smokers.…”
Section: Discussionmentioning
confidence: 99%